Implications of Achieving TICI 2b Versus TICI 3 Reperfusion in Patients With Ischemic Stroke: A Cost-Effectiveness Analysis. (1st September 2019) - Wu, Xiao; Gandhi, Dheeraj; Matouk, Charles C; Schindler, Joseph; Hughes, Danny; Forman, Howard; Sanelli, Pina C; Malhotra, Ajayy
Abstract: INTRODUCTION: The degree of successful reperfusion of large vessel occlusions (LVO) in patients with acute ischemic stroke (AIS) treated by mechanical thrombectomy (MT) is one of the critical and potentially modifiable determinants of clinical outcome. Differences in outcomes between patients with TICI 2b vs TICI 3 reperfusion have recently been highlighted. This study examines the public health and cost implications of achieving TICI 2b vs TICI 3 reperfusion. METHODS: A decision-analytic study was performed to estimate the lifetime quality-adjusted life years (QALY) and associated costs based on the degree of reperfusion achieved. The base case calculations and multiple one-way sensitivity analyses were performed for AIS patients with LVO undergoing MT in 3 age groups: 55, 65, and 75 yr old, respectively. RESULTS: Within 90 d, achieving TICI 3 results in a cost-saving of $5, 258 per patient and health benefit of 7.3 d in perfect health as compared to TICI 2b. In the long-term, for the 3 ages groups (55, 65, and 75 yr old), achieving TICI 3 results in cost savings of $82, 965, $51, 155, and $31, 034 respectively, and health benefits of 2.42 QALYs, 1.92 QALYs, and 1.36 QALYs. Every 1% increase in TICI 3 in 55-yr-old patients at a nation-wide level results in a cost saving of nearly $6.1 million and a health benefit of 176 QALYs. Among 65-yr-old patients, the corresponding cost savings and health benefit are $3.7 million and 176 QALYs, and $2.3 million and 99 QALYS for 75-yr-old patients. CONCLUSION: There are substantial cost and health implications of achieving complete vs incomplete reperfusion after EVT. Our study reinforces the need for a more conservative definition of therapy success and treatment approaches to achieve TICI 3 reperfusion.